2007
DOI: 10.1017/s0954579407000417
|View full text |Cite
|
Sign up to set email alerts
|

Resilience among children and adolescents at risk for depression: Mediation and moderation across social and neurobiological contexts

Abstract: This article offers a multilevel perspective on resilience to depression, with a focus on interactions among social and neurobehavioral systems involved in emotional reactivity and regulation. We discuss models of cross-contextual mediation and moderation by which the social context influences or modifies the effects of resilience processes at the biological level, or the biological context influences or modifies the effects of resilience processes at the social level. We highlight the socialization of emotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(113 citation statements)
references
References 164 publications
(184 reference statements)
4
103
0
6
Order By: Relevance
“…For understanding the relationship between resilience and depression, a multilevel perspective is necessary. As Silk et al [26] discussed, mediation and moderation across social and neurobiological contexts influence the effects of resilient processes. In the context of psychiatric hospitals, it is likely that the level of workplace adversity has the potential to influence the benefits of resilience processes against depression.…”
Section: Discussionmentioning
confidence: 99%
“…For understanding the relationship between resilience and depression, a multilevel perspective is necessary. As Silk et al [26] discussed, mediation and moderation across social and neurobiological contexts influence the effects of resilient processes. In the context of psychiatric hospitals, it is likely that the level of workplace adversity has the potential to influence the benefits of resilience processes against depression.…”
Section: Discussionmentioning
confidence: 99%
“…This points to the possibility for high sleep quality being a protective factor in the development of depressive symptoms. One longitudinal study provided support for this idea by showing that resilient young adults who did not develop depressive symptoms (despite low socioeconomic status) demonstrated shorter sleep latency and enhanced deep sleep (both indicators of better sleep) during childhood (Silk et al, 2007). …”
Section: Sleep As a Moderator Of The Link Between Cvc And Depressive mentioning
confidence: 99%
“…In fact, several studies have found that some protective factors are diminished in the context of severe neighborhood disadvantage (Silk et al 2007;Stouthamer-Loeber et al 2002), with differences emerging between low income urban neighborhoods and inner city neighborhoods or projects Shaw et al 2004). Thus it is important to determine whether protective factors work similarly across levels of neighborhood disadvantage, or whether the benefits are limited to specific contexts.…”
Section: Positive Outcomementioning
confidence: 99%